Palabras clave para el constitucionalismo de hoy - una perspectiva alemana - Häberle, Peter (2015)
After what happened in 1989, the doctrine states that we are now in the “World Time of the Constitutional State”. But what are the implicationsof this? How has this impacted on the dispute of the German doctrine about the right comprehensionof the nature of the Constitution? Which shouldbe the labor of a Public Law and International Law professor in this context?In the present article, the author comments the indicated phenomenon, and, in order to do this, he uses figures such as the Cooperative Constitutional State, or the living constitutions. Constitutions, he states, aren’t just a product of constitutionalism, but many other factor must be taken into account.